Distribution status and habitat characteristics of the endangered freshwater fish, Microphysogobio rapidus (Cyprinidae). Issue 4 (4th July 2017) - Hong, Yang-Ki; Sung, Ha-Cheol; Ko, Myeong-Hun; Kim, Keun-Sik; Bang, In-Chul
ABSTRACT: To investigate distribution, habitat characteristics, and current conservation status of the endangered endemic species, rapid small gudgeon Microphysogobio rapidus (Cyprinidae), we surveyed a total of 79 sites from the historic records (20 sites) plus additional sites (59 sites) with good habitat conditions, analyzed their sites, and compared them with historic recorded sites to reveal the factors of extinction threats and causes. We found only eight out of 79 sites in the Nam River areas. The habitats were greatly reduced and restricted compared with the historic sites, which mainly cause from habitat modification, such as various types of river renovations at the main stream and tributary streams of the Nakdong River. The present habitats are higher water temperature and more number of fish species than the absent ones, but conductivity, total nitrogen, and number of weir are lower. In addition, the present sites are lower low velocity at pool and higher mean substrate at pool. From this study, we suggest that maintaining good water quality and preventing anthropogenic impacts greatly aid conservation of the M . rapidus in South Korea.